Fine spectra of upper triangular double-band matrices - Karakaya, Vatan; Altun, Muhammed (ELSEVIER SCIENCE BV, 2010)
The fine spectra of lower triangular double-band matrices have been examined by several authors (e.g.[13,22]). Here we determine the fine spectra of upper triangular double-band matrices over the sequence spaces c(0) and c. Upper triangular double-band matrices are infinite matrices which include the left-shift, averaging and difference operators. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Spectrum of an operator; Infinite matrices; Sequence spaces; CESARO OPERATOR; Mathematics